A body‐mounted device for MRI‐guided spinal therapy. Issue 2 (20th February 2021) - Squires, Alexander; Hovet, Sierra; Li, Rui; Oshinski, John; Ho Tse, Zion Tsz
Abstract: Background: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease with no cure and limited treatment options. Recent studies have shown that delivering cellular therapeutics to the ventral horn of the spinal cord can effectively halt neurodegeneration associated with ALS in small animal models. Methods: We developed a robotic system that assists with MRI‐guided percutaneous injections to the spinal cord. The needle positioning robot consists of two linear axes with motorised translational sleds for two‐degree‐of‐freedom (2‐DOF) needle translation and a radial template for 2‐DOF discrete rotation. Results: The robot's targeting capability, evaluated using phantom models and swine cadavers, showed mean targeting errors of 0.48 and 2.84 mm, respectively. The duration of the targeting procedure is approximately 60 min, with an extra 10 min for each additional injection. Conclusions: The presented robot does not affect imaging quality during MRI‐guided procedures, and it enables a simplified workflow for MRI‐guided spinal therapy.